X‐Ray Nanoanalysis Revealing the Role of Electronically Active Passivation Layers in Perovskite X‐Ray film Detectors - Matteo Verdi; Andrea Ciavatti; Jaime Segura‐Ruiz; Laura Basiricò; Roberto Sorrentino; Isabel Pinto Goncalves; Annamaria Petrozza; Federico Boscherini; Beatrice Fraboni (Advanced Electronic Materials, 2023)
Abstract X‐ray direct detectors based on hybrid lead‐halide perovskite have seen a dramatic increase of interest in the last years. A rush for the achievement of high performing devices drives the scientific community. In this context, several photoconductor sensors employ functional layers to increase the gain effect, but the full comprehension of the mechanism is still lacking. Here, X‐ray nanoanalysis is used, performed by simultaneous acquisition of X‐ray Fluorescence and X‐ray Beam Induced Current maps, to investigate at the nanoscale level the role of [6,6]‐phenyl‐C61‐butyric acid methyl ester fullerene (PCBM) molecules when interacting with MAPbI3 polycrystalline thin films acting as photo‐conductors in X‐ray detectors. At the device‐scale level it shows that the addition of PCBM enhances the X‐ray sensitivity by four times. At the nanoscale level how the perovskite grain boundaries act as high photocurrent generation centers is demonstrated. The addition of the PCBM increases the photocurrent generation, as the macroscopic performance does, and the charge collection becomes uniform over the full crystallite volume. The results clarify the role of grain boundaries and charge selecting layers and establish the X‐ray nanoanalysis techniques as a powerful tool to investigate charge transport and collection in perovskite films.